Ice hockey forward skating force-velocity profiling using single unloaded vs. multiple loaded methods - Perez, J.; Guilhem, G.; Brocherie, F. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to compare skating force-velocity relationships determined throughout sprints performed against various loaded conditions or inferred from movement kinetics measured during a single unloaded sprint. Ten female ice hockey players performed one unloaded maximal skating sprint test measured with a radar gun followed by 4 resisted skating sprints against a robotic horizontal resistance with progressive loads in reference to equipped body mass (BM): 3 kg (robotic resistance), 25, 50, and 75% of equipped BM. Maximal theoretical force (F0), velocity (V0), power (Pmax), optimal velocity (Vopt) condition for producing maximal power, and slope of the linear force-velocity relationship (SFV) were determined from each method and compared using a paired sample t-test, absolute mean bias (±95% confidence intervals), Pearson correlations, and typical error of the estimate in standardized units (effect size [ES]). Statistical significance was set at p < 0.05. No statistical difference was found for all mechanical variables determined from the 2 methods (p ranging 0.09-0.59). Although exhibiting positive correlations ranging from moderate (r = 0.50 for SFV) to high (r ranging from 0.71 to 0.84 for F0, V0, Vopt, and Pmax) between methods, all variables exhibited large levels of error between approaches (ES ranging 0.66-1.71). Multiple loaded and single unloaded methods were comparable with determine force-velocity relationships during forward on-ice skating sprint. The low-cost fatigue-free unloaded method suggests it could be used in constrained contexts (i.e., congested schedule and low available time) or for a simple force-velocity profiling. Inversely, multiple loaded methods would be more appropriate to evaluate and individualize training for skilled ice hockey players accustomed to resistive skating sprint.